THE ROLE OF SOCIAL SERVICES IN FOSTERING VAGRANTS AND BEGGARS IN PEKANBARU CITY (Case Study at Intersection 4 Panam) - Mega Fadilla Husna Batubara; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
This thesis examines the role of social services in the rehabilitation of homeless individuals and beggars in Pekanbaru City. The research aims to explore how the Social Service addresses the increasingly prevalent social issues related to homelessness and begging, which involve not only residents but also individuals from other regions, such as Payakumbuh and Jakarta. The methodology employed in this study is qualitative, utilizing data collection through interviews and direct observations of the individuals involved. The findings indicate that social services play a crucial role in providing social rehabilitation and programs aimed at improving the quality of life for people experiencing homelessness and those who beg. These programs include education, skills training, and psychological support designed to reintegrate them into society. Furthermore, this research emphasizes the importance of collaboration between the government and the community in creating a supportive environment for rehabilitation. In conclusion, this thesis highlights the need for effective interventions from social services to address the challenges faced by homeless individuals and beggars, while also promoting ongoing efforts to enhance their welfare in Pekanbaru.